The timely decision for businesses in Uganda to adopt modern technology in the new world setting - Kayemba, Joseph (Gateway Research Centre, 2020)
2019 will be remembered as the year the world was hit by an originally unknown and remorseless disease. By 2020, the whole world was locked down because of Coronavirus pandemic. Everything changed including the way businesses are conducted. However, the existence of modern technology seemed to have provided an answer to most of the businesses especially in the manner in which they are run and how they connect with their customers, suppliers and other stakeholders including regulatory authorities. The situation became abnormal but technology has become the order of the day in the new normal. The brief presents the potential role of digital technologies, focusing on their influence in the business world in the post COVID-19 era. There are many emerging issues and it is pertinent to find ways of using technology to address them considering the Covid-19 recess and the Post Covid period. How can technologies be advantageous in the emerging social challenges? Businesses should be able to adapt to new business models which embrace technology as the pivot for business management, growth and trajectory.